A Comparative Study on Students’s English Listening Strategies In SV-UGM and CDTC - Cisya Dewantara Nugraha; Liping Jia (Jurnal Gama Societa, 2017)
This study attempts to identify the use of listening strategies by technical and vocational college non-English majors, explore the relationship between listening strategies and listening proficiency and investigatethe difference between good and poor learners in the use of listening strategy to provide some pedagogicalimplications for teachers to guide the students to select, manage and adjust their listening strategies effectivelyin order to improve autonomous learning abilities, learning efficiency and English proficiency. The subjects inthe study are 75 first-year vocational college non-English majors from Chengdu Textile College and SV-UGM.First, all the participants took the model listening comprehension test. Second, the participants were given halfan hour to complete the questionnaire after finishing the model test. Thirdly, 10 students from both groups ofparticipants were interviewed individually for further information in the use of listening strategies and alsoexplore the relationship between the students’ listening strategy use. Finally, all the data was collected, andwas processed by SPSS22.0, then was analyzed as answers to the research questions. The result shows thatIndonesian students are more inclined to ask questions for explanation and verification. Furthermore, theyfocus on cooperative learning, which promotes a greater use of learning strategies than individual learning.However, Chinese learners are inclined to study English by themselves and get used to independent study. Theywould ask for help unless they meet some problems which cannot be solved by their own effort.